Does radiation therapy affect adhesion of tricalcium silicate cements to root dentin? - Lochan KHULLAR; Nidambur Vasudev BALLAL; Tan Fırat EYÜBOĞLU; Mutlu ÖZCAN (University of São Paulo, 2023)
Abstract Objective This study aimed to analyze the effect of irradiation on the push-out bond strength of mineral trioxide aggregate (MTA) and Biodentine to radicular dentin. Methodology A total of 60 extracted mature human teeth with single root canals were categorized into two groups (irradiated and non-irradiated) (n=30). Each group was further divided into two sub-groups based on cements used (Biodentine and MTA). Then, a cumulative radiation dose of 60 Gy was divided into 30 fractions (two Gy for every fraction) and administered for five successive days per week over six weeks. Obturation was then performed using MTA and Biodentine. Afterwards, 1.5 mm thick horizontal sections were procured from the middle one-third of all the specimens and then subjected to push-out bond test. Results were analyzed using one-way analysis of variance with post-hoc Tukey's test. Results The bond strength of Biodentine and MTA to irradiated teeth was lower than non-irradiated teeth. Highest push-out bond strength was observed in non-irradiated specimens filled with Biodentine (p=0), followed by irradiated specimens filled with Biodentine (p=0); non-irradiated specimens filled with MTA (p=0); and irradiated specimens filled with MTA (p=0.9). Conclusion The push-out bond strength of Biodentine and MTA to root canal dentin decreased significantly post irradiation.